Esfandiar Beg, the ruler of Sinub city and his role in protecting the power of Mirgah Jandari from destruction (794-843 AH/1392-1440 AD) - a historical-political study - Hussein, Dr. Hazhar Abdullah (Sulaimani Journal for Humanities, 2026)
Esfandiar Beg was one of the members of the Jandari Mirgha, which was established in the late 7th century AD in northern Anatolia on the Black Sea coast Jandari is a creature. However, at the end of the same period, this empire came under pressure and attacks of the Ottomans in order to take over the lands of this empire and end it like other emirates of Anatolia They captured the capital of the Mirgah, the city of Qastamun, and thus the Jandari Mirgah was close to destruction, but with the presence of the governor of Sinub Esfandiar Beg and his political and military efforts, he was able to save the Mirgah from destruction. After the transfer of the authority of the Jandari Mirga to Esfandiar Beg, Esfandiar Beg established the city of Sinub as the capital of the Mirga, and began his own political relations to restore the lost Mirga lands, and for this purpose in an external alliance In order to compete with the Ottomans with his help, Esfandiar Beg was able to do this again in the late 8th and early 15th centuries, with the appearance of Timur Langi and his forces in Anatolia and his victory over the Ottomans He was able to restore the borders of Mirgah as a starting point and lay a strong foundation. He was also able to carry out many development, scientific and civil works in Mirgah.
Keywords: Jandali; Ottoman; Anatolia; Sinope; Esfandiari Bey